![3(y - 1) - 4( - 2) = 6 3(y - 1) - 4( - 2) = 6](https://tex.z-dn.net/?f=3%28y+-+1%29+-+4%28+-+2%29+%3D+6)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
3(y — 1) — 4(—2) = 6
3y — 3 + 8 = 6
3y + 5 = 6
3y = 6 — 5
3y = 1
y = 1/3
Espero ter ajudado bastante!)
rover123:
obgd❤❤
Perguntas interessantes
Geografia,
10 meses atrás
Português,
10 meses atrás
Geografia,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás